2017
DOI: 10.1017/s0068113x17000113
|View full text |Cite
|
Sign up to set email alerts
|

London's Hadrianic War?

Abstract: Recent work has advanced our understanding of human crania found in London's upper Walbrook valley, where skull deposition appears to have peaked during the occupation of the Cripplegate fort, itself probably built soon after London's Hadrianic fire. Although this fire is usually considered to have been accidental, parallels can be drawn with London's Boudican destruction. This article explores the possibility that these three strands of Hadrianic evidence — fire, fort and skulls — find common explanation in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(18 reference statements)
0
3
0
Order By: Relevance
“… 35 Perring 2017, 61. Perring also cited scholars who had suggested that the issues minted at Alexandria in a.d .…”
mentioning
confidence: 99%
“… 35 Perring 2017, 61. Perring also cited scholars who had suggested that the issues minted at Alexandria in a.d .…”
mentioning
confidence: 99%
“… 11 Shepherd 2012; Perring 2017, 52–5. Construction of the fort is dated by samian to the 120s, but the absence of Hadrianic fire debris suggested to Perring that it may have been built after the fire dated c .…”
mentioning
confidence: 99%
“… 70 Bradley and Gordon 1988; Edwards et al . 2009; Knűsel and Carr 1995; Marsh and West 1981; Schulting and Bradley 2013; Redfern and Bonney 2014; Perring 2017; Harward et al 2015.…”
mentioning
confidence: 99%